Implementasi Metode Pembelajaran Diskusi Kelompok Terhadap Hasil Belajar Fisika Peserta Didik - Kholida Ismatulloh; Ropikoh Ropikoh; Yosi Nur Kholiso (Kappa Journal, 2022)
The study aimed to find out how the physics learning outcomes of class VII students of SMPN 3 Selong increase in terms of temperature and heat. The research subjects were class VII students at SMPN 3 Selong, namely Class VII B and VII C, with the data collection process using a cognitive test in the form of a written test in the form of an essay totaling 10 questions. The average value obtained in the experimental class using the group discussion method obtained an average value of 77.85, while in the control class using conventional methods obtained an average value of 55.60 with a difference in value of 22.25 points. The hypothesis calculation obtained a t_count value of 3.052 while a t_table of 1.092. From the results of the calculation of the hypothesis test for physics learning outcomes in the subject of temperature and heat for class VII students of SMPN 3 Selong, the value is ?ℎ?????>??????, then the alternative hypothesis (Ha) is accepted. So it can be concluded that there is an increase in physics learning outcomes for class VII students in implementing it using the group discussion method.